Big star fallin' mama : five women in black music - Jones, Hettie (New York : Viking Press, 1974)
Portraits of five black women and the kind of music they sang during a period of social change. Includes Ma Rainey, Bessie Smith, Mahalia Jackson, Billie Holiday, and Aretha Franklin.
Discography: p. 139-140
Bibliography: p. 137-138
Keywords: Afro -- American women musicians -- Juvenile literature; Blues (Music) -- Juvenile literature